Induction chemotherapy for locally advanced thymic epithelial tumors: consideration from the RYTHMIC prospective cohort - Nakagawa, Kazuo (Mediastinum; Vol 3 (April 2019): Mediastinum, 2019)
Thymic epithelial tumors (TETs) are rare neoplasms that are highly heterogeneous, ranging from indolent to highly aggressive (1). Surgery has been the mainstay of treatment and complete resection of a tumor is one of the most important prognostic factors (2). Masaoka’s staging system has been widely used for a long time (3). According to this system, patients with stage I or II disease have an excellent prognosis (4).